ENVIRONMENTAL CONSCIOUSNESS FORMATION AS A RESPONSE TO THE CURRENT CHALLENGES - Chenbai, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The challenges of the global order prove that it is environmental issues that demonstrate the level of self-awareness of both society as a whole and the individual. The idea that the vital need of today is the formation of ecological consciousness and the need to green all its other forms is substantiated in the works on the philosophical problems of ecology. The aim and tasks. The aim of this study is to identify the content of the phenomenon of ecological consciousness, as well as those transformations in culture and civilization that provoked the development of ecological philosophy. The aim and tasks. The theoretical foundations of the study are the works of philosophers and scientists who analyzed the transformations in European culture that changed man's attitude to nature. It will be appropriate to apply the method of comparative analysis, as well as system-logical and structural research methods. Research results. The analysis of the main causes of global problems requires a return to the times when philosophers and scientists began to cover the transformations of society and the individual, which, they said, led to spirituality and practicality. The essence of modern world problems must be sought not in external factors, but in man. The social consciousness has finally accepted the threat of a planetary catastrophe as real. Specialists in various fields of science make every effort to find ways to solve environmental problems. An important result of many studies has been the necessary realization to develop a paradigm of progress that would be based on self-restraint, on changing the types of production in order to reduce its growth. Discussion Mankind has a close ecological, demographic connection, without feeling the unity in the cultural and civilizational sense. Modern civilizations are at different levels of economic development and therefore have different opportunities in solving environmental problems. In philosophical studies of ecology the position on necessity of formation of ecological consciousness is substantiated. Environmental philosophy as a separate area of research which aims to develop a strategy of action that will at least slow down, if not stop the deepening of the current environmental crisis is being actively developed. The problem of coevolution of man and the biosphere is fundamental to ecological philosophy.